2020
DOI: 10.1186/s12920-020-00742-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic colocalization atlas points to common regulatory sites and genes for hematopoietic traits and hematopoietic contributions to disease phenotypes

Abstract: Background: Genetic associations link hematopoietic traits and disease end-points, but most causal variants and genes underlying these relationships are unknown. Here, we used genetic colocalization to nominate loci and genes related to shared genetic signal for hematopoietic, cardiovascular, autoimmune, neuropsychiatric, and cancer phenotypes. Methods: Our aim was to identify colocalization sites for human traits among established genome-wide significant loci. Using genome-wide association study (GWAS) summar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Multivariable and mediation analyses on other blood traits identified cross-mediating opposing effects of WHR and BMI on quantitative blood counts across cell lineages (Figure 1d,e,f and lineages suggested that underlying mechanisms related to hematopoietic stem and progenitor cells (HSCs) common to these lineages (Thom and Voight, 2020) (Figure 1g). These findings also argued against gender-related effects: although men generally have higher hemoglobin (Vuckovic et al, 2020) and WHR (Pulit et al, 2019), women have higher platelet and neutrophil counts (Bain, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable and mediation analyses on other blood traits identified cross-mediating opposing effects of WHR and BMI on quantitative blood counts across cell lineages (Figure 1d,e,f and lineages suggested that underlying mechanisms related to hematopoietic stem and progenitor cells (HSCs) common to these lineages (Thom and Voight, 2020) (Figure 1g). These findings also argued against gender-related effects: although men generally have higher hemoglobin (Vuckovic et al, 2020) and WHR (Pulit et al, 2019), women have higher platelet and neutrophil counts (Bain, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Multivariable and mediation analyses on other blood traits identified cross-mediating opposing effects of WHR and BMI on quantitative blood counts across cell lineages (Figure 1d,e,f and lineages suggested that underlying mechanisms related to hematopoietic stem and progenitor cells (HSCs) common to these lineages (Thom and Voight, 2020) (Figure 1g). These findings also argued against sex-related effects.…”
Section: Genetic Impacts Of Whr Oppose Bmi Effects On Blood Trait Var...mentioning
confidence: 99%
“…The 3 rd definitive wave produces the hematopoietic stem cells (HSCs) that seed the fetal liver and bone marrow to ultimately yield adult-type red blood cells expressing adult hemoglobin, megakaryocyte, myeloid and lymphoid cells throughout life. In addition to the hematopoietic system, blood cells contribute to development and complex disease pathology in virtually all other organ systems [ 20 ]. For example, tissue-resident macrophages help to orchestrate tissue development, homeostasis, and repair throughout the body [ 16 , 17 ].…”
Section: Ontogeny Of Hematopoiesis and Its Relation To Ipsc-derived Mmentioning
confidence: 99%
“…For example, tissue-resident macrophages help to orchestrate tissue development, homeostasis, and repair throughout the body [ 16 , 17 ]. In addition to autoimmune and cancer risks, hematopoietic cell types impact neuropsychiatric and cardiovascular disease [ 20 ].…”
Section: Ontogeny Of Hematopoiesis and Its Relation To Ipsc-derived Mmentioning
confidence: 99%
See 1 more Smart Citation